Can Perspective-Taking Reduce Crime? Examining a Pathway Through Empathic-Concern and Guilt-Proneness. (December 2014) - Martinez, Andres G.; Stuewig, Jeffrey; Tangney, June P.
We describe and appraise a theoretical model in which individual differences in perspective-taking eventuate in crime reduction. Specifically, it is hypothesized that perspective-taking propensities influence the tendency to feel empathic-concern, thereby heightening proneness for guilt, which ultimately inhibits criminal behavior (perspective-taking → empathic-concern → guilt-proneness → crime desistance). Data from two sources were analyzed: (a) a cross-sectional college sample and (b) a longitudinal sample of jail inmates. Overall, results lend credence to this theoretical model: Perspective-taking propensities ultimately "put the brakes" on criminal behavior—via an emotional pathway of empathic-concern and then guilt-proneness. Discussion focuses on the nature of perspective-taking, its generative role for moral emotion and behavior, as well as potential applications for crime reduction.